Effet insecticide de l'huile essentielle de Mentha pulegium L. à l'égard du bioagresseur Tribolium confusum des denrées stockées - RAHMANI, Yousra (My University, 2021)
The use of chemical control methods in cereal crops appears to be responsible for many adverse effects on the crops themselves and especially on human health. The search for alternative methods of protection of stored commodities against wheat pests, in particular the insect Tribolium confusum, insect pest of durum wheat (Triticum durum) is in constant development with the aim of reducing the toxicities that result from these chemicals. One of these alternative methods is the use of bio-insecticide. More specifically, the use of the insecticide effect of the essential oil of botanical substrates. The plant used in our work is Mentha pulegium L, which is called "Fluo" or " فليو " vernacular. Our study involves extracting essential oil from the leaves of this plant and determining its insecticidal effect against adults of Tribolium confusum. As a result, mortality tests were conducted by direct contact and inhalation of EO. The repellent effect of this oil was also tested against the insect and the germination effect of treated wheat kernels (Triticum durum). The LD 50 of the tests varied between 6.02 and 6.08μl/ml in a period that did not exceed 24 hours. The repulsion rate was also high with an average of 82.22% after 2hours for all doses performed. The germination rate assumed poor values with an average of 46%. Our results demonstrated the effectiveness of Mentha pulegium L. essential oil as an alternative means of control of stored food pests.
Keywords: Durum wheat (Tritium durum), Mentha pulegium L., Tribolium confusum, essential oil.